Tissue Culture of Purple Sweet Potato Using Murashige and Skoog (MS) Medium Based on Benzyl Amino Purine (BAP) : Kultur Jaringan Ubi Jalar Ungu Menggunakan Media Murashige dan Skoog (MS) Berbasis Benzyl Amino Purine BAP - Nurul Fajriyah, Walak; Syarifah Ainy, Noer; Hadi, Nestiyanto (Jurnal Ilmiah Biologi Eksperimen dan Keanekaragaman Hayati (J-BEKH), 2025)
Purple sweet potato (Ipomoea batatas L.) is one of the local food sources rich in anthocyanins and has great potential to be developed through tissue culture techniques. This study aimed to determine the effect of Benzyl Amino Purine (BAP) on the growth of purple sweet potato explants cultured in vitro using Murashige and Skoog (MS) medium. The experiment was conducted using a Completely Randomized Design (CRD) with four BAP concentration treatments (0, 2.5, 3.5, and 5.0 mg/L), each replicated five times, resulting in 20 experimental units. The explants used were stem segments of purple sweet potato (Ipomoea batatas L.). The explants were then cultured on solid Murashige and Skoog (MS) medium containing BAP for 8 weeks. Observed parameters included plant height, callus height, and the percentage of explants forming callus. The results showed that the 3.5 mg/L BAP treatment (N2) produced the best growth, with an average plant height of 2.7 mm, callus height of 1.6 mm, and 100% callus formation. Statistical analysis indicated that BAP application had a significant effect on all observed parameters. Therefore, a concentration of 3.5 mg/L BAP is recommended as the optimal treatment for in vitro propagation of purple sweet potato.